INFERENSI STATISTIK DARI DISTRIBUSI NORMAL DENGAN METODE BAYES UNTUK NON-INFORMATIF PRIOR - Prahutama, Alan; Sugito, Sugito; Rusgiyono, Agus (MEDIA STATISTIKA, 2012)
One of the method that can be used in statistical inference is Bayesian method. It combine sample distribution and prior distribution to get a posterior distribution. In this paper, sample distribution used is univariate normal distribution. Prior distribution used is non-informative prior. Determination technique of non-informative prior use Jefrrey’s method  from univariate normal distribution. After got the posterior distribution, find the  marginal distribution of mean and variance. So that will get the parameter estimation of interval for mean and variance. Hypothesis testing for mean and variance can find from parameter estimation of formed interval.   Keywords: Bayesian method, non-informatif prior, Jeffrey’s method, Parameter Estimation of Interval, Hypothesis test